Undiagnosed coeliac disease does not appear to be associated with unfavourable outcome of pregnancy. Issue 1 (18th December 2003) - Greco, L; Veneziano, A; Di Donato, L; Zampella, C; Pecoraro, M; Paladini, D; Paparo, F; Vollaro, A; Martinelli, P
Abstract : Background: In a previous hospital based study, we suggested that undiagnosed coeliac disease has a prevalence, among pregnant women, of 1:80, and is a cause of unfavourable outcome of pregnancy. Aims: In order to confirm or dismiss this hypothesis, which has significant public health implications, we carried out a large population based study on a stratified sample from the whole Campania region. Patients: During the period of the study, 5345 women were admitted to the OBS-GYN wards regional network: 5055 (95%) were enrolled in the study. Methods: Antihuman IgA class antitissue transglutaminase (TGASE) antibodies were tested by an ELISA method. Endomysial antibodies (EMA) were investigated on thin sections of human cord blood by an immunofluorescence test. The HLA class II DQA1*0501/DQB1*02 and DQA1*0301/DQB1*0302 haplotypes were assessed using the Eurospital Eu-DQ kit. Duodenal biopsy was not considered feasible by the ethics committee for pregnant women near delivery. Results: Fifty one of 5055 patients had confirmed positive results. We added to these 12 women with known coeliac disease, giving a prevalence rate for coeliac disease of 1:80 (exactly the value observed during the first study). Comparing the 51 TGASE positive with 4997 negative women, we did not observe an excess risk of abortion, premature delivery, small birth weight, or intrauterine growth retardation. Anaemia was more frequent in cases than controls. Conclusions: Undiagnosed coeliac disease is frequent among pregnant women (>1%) but is not associated with an unfavourable outcome of pregnancy.